Integrating civil society into regional innovation systems - a social foresight lab approach. (2nd September 2020) - Schroth, Fabian; Glatte, Hannah; Kaiser, Simone
In this article, we address the challenge of embedding local knowledge in non-spatially defined innovation systems. We argue that this can be achieved via the inclusion of local civil society in innovation processes. The local population has knowledge of local challenges and potential, and is capable of developing locally relevant ideas. Embedding this knowledge in innovation processes requires a special set of methods that enable local actors to gain access to innovation processes and develop ideas, formulate challenges and identify potential opportunities on equal footing with other innovation actors. In this paper, we present such an approach in the form of a social foresight lab, as used in the context of technology transfer in rural areas to facilitate the identification of local challenges and potential, the collaborative development of ideas, and the regional embedding of non-spatially defined innovation processes. The principles underlying the above are experimentation, collaboration and real-world embeddedness.